SOCIAL PUBLIC POLICIES AND SUSTAINABLE DEMOCRACY: CHALLENGES AND PARADOXES IN THE CONTEXT OF REDEMOCRATIZATION IN BRAZIL (REMUNOM, 2026)
This research analyzes how social public policies are influenced by fluctuations in the stability of the Brazilian Democratic Rule of Law, from 1985 to 2024. Methodologically, it is a basic research, qualitative in approach, theoretical in genre, descriptive in objective, and bibliographic in procedural method. To aid in the research, the Varieties of Democracy index (V-Dem, 2025) was used, which evaluates democracy from 0 to 1 (1 being the most democratic), based on the electoral, liberal, deliberative, participatory, and egalitarian dimensions, comparing this score with historical events in Brazil. The results reflect the highest score for the period from 1992 to 2015, with averages of 0.86; 0.74; 0.61; 0.77; and 0.60, respectively, for the aforementioned dimensions. During this period, there was greater popular participation and contribution to the construction of public policies, such as bills approved through popular initiative, the Popular Housing Law (Law 11.124/2005) and the Clean Record Law (LC 135/2010), in addition to programs benefiting the population. The average for the period from 2016 to 2022 was established as follows, respectively: 0.73; 0.58; 0.47; 0.53; 0.43. This interval was notable for the dismantling of public policies caused by the Spending Cap Law (Constitutional Amendment No. 95/2016). It is concluded that there is a tendency for democratic stability with respect to social and fundamental rights to influence the development and monitoring of public policies.